A Robust, Recyclable Resin for Decagram Scale Resolution of (±)‐Mefloquine and Other Chiral N‐Heterocycles. Issue 4 (11th December 2015) - Kreituss, Imants; Chen, Kuang‐Yen; Eitel, Simon H.; Adam, Jean‐Michel; Wuitschik, Georg; Fettes, Alec; Bode, Jeffrey W.
Abstract: Decagram quantities of enantiopure (+)‐mefloquine have been produced via kinetic resolution of racemic mefloquine using a ROMP‐gel supported chiral acyl hydroxamic acid resolving agent. The requisite monomer was prepared in a few synthetic steps without chromatography and polymerization was safely performed on a >30 gram scale under ambient conditions. The reagent was readily regenerated and reused multiple times for the resolution of 150 grams of (±)‐mefloquine and other chiral N‐heterocylces. Abstract : Pearl Jam : A novel ROMP‐gel supported reagent allows the preparation of enantiopure (+)‐ erythro‐ mefloquine on a decagram scale from its racemate. The monomer synthesis does not require chromatographic purification, and polymerization can be carried out safely on a >30 gram scale. PEARL is readily recovered after each cycle and has been applied for resolution of a broad range of N‐heterocycles.